Experimental Myocardial Infarction Elicits Time-Dependent Patterns of Vascular Hypoxia in Peripheral Organs and in the Brain - David, Hélène; Ughetto, Aurore; Gaudard, Philippe; Plawecki, Maëlle; Paiyabhroma, Nitchawat; Zub, Emma; Colson, Pascal; Richard, Sylvain; Marchi, Nicola; Sicard, Pierre (Frontiers in Cardiovascular Medicine, 2021)
Aims: Microvascular alterations occurring after myocardial infarction (MI) may represent a risk factor for multi-organ failure. Here, we used in vivo photoacoustic (PA) imaging to track and define the changes in vascular oxygen saturation (sO2) occurring over time after experimental MI in multiple peripheral organs and in the brain. Methods and results: MI was obtained in BALB/c mice by permanent ligation of the left anterior descending artery. PA imaging (Vevo LAZR-X) allowed tracking mouse-specific sO2 kinetics in the cardiac left ventricular (LV) anterior wall, brain, kidney and liver at 4h, 1 day and 7 days post-MI. Here, we reported a correlation between LV sO2 and longitudinal anterior myocardial strain after MI (r=-0.44, p<0.0001, n=96). Acute LV dysfunction was associated with global hypoxia, specifically a decrease in sO2 level in the brain (-5.9 %), kidney (-6.4 %) and liver (-7.3 %) at 4h and 24h post-MI. Concomitantly, a preliminary examination of capillary NG2DsRed pericytes indicated cells rarefication in the heart and kidney. While the cardiac tissue was persistently impacted, sO2 levels returned to pre-MI levels in the brain and in peripheral organs 7 days after MI. Conclusions: Collectively, our data indicate that experimental MI elicits precise trajectories of vascular hypoxia in peripheral organs and in the brain. PA imaging enabled the synchronous tracking of oxygenation in multiple organs and occurring post-MI, potentially enabling a translational diagnostic modality for the identification of vascular modifications in this disease setting.